2006
DOI: 10.1038/sj.npp.1301102
|View full text |Cite
|
Sign up to set email alerts
|

GABAB Receptor-Positive Modulation Decreases Selective Molecular and Behavioral Effects of Cocaine

Abstract: Exposure to cocaine induces selective behavioral and molecular adaptations. In rodents, acute cocaine induces increased locomotor activity, whereas prolonged drug exposure results in behavioral locomotor sensitization, which is thought to be a consequence of druginduced neuroadaptive changes. Recent attention has been given to compounds activating GABA B receptors as potential antiaddictive therapies. In particular, the principle of allosteric positive GABA B receptor modulators is very promising in this respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
35
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 60 publications
4
35
0
1
Order By: Relevance
“…These present results are consistent with previous data showing that GABA B receptor-positive modulator blocked the establishment but not the expression of behavioral sensitization to cocaine (Lhuillier et al, 2007). This absence of effects of GS39783 on the expression of CPP might be attributed to the inability of GABA B receptor-positive modulator to affect conditioned motivational properties of nicotine-paired cues.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…These present results are consistent with previous data showing that GABA B receptor-positive modulator blocked the establishment but not the expression of behavioral sensitization to cocaine (Lhuillier et al, 2007). This absence of effects of GS39783 on the expression of CPP might be attributed to the inability of GABA B receptor-positive modulator to affect conditioned motivational properties of nicotine-paired cues.…”
Section: Discussionsupporting
confidence: 93%
“…in a suspension of 0.5% methylcellulose at a volume of 5 ml/kg 30 min before testing. Doses of GS39783 were chosen based on our previous data showing that GS39783 can reverse the behavioral and molecular effects of cocaine in this dose range (Slattery et al, 2005;Lhuillier et al, 2007). Furthermore, they are in line with the pharmacokinetic properties of GS39783 in terms of brain exposure (Smith et al, 2004).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A possible strategy to potentiate the effects of baclofen may come from the use of PAMs. These compounds possess behavioral activity similar to that of the full GABA B receptor agonists, including in tests related to SUDs [97,178,179,180,181,182]. Preclinical studies have demonstrated that when coadministered with baclofen, PAMs enhance its potency, which could in theory minimize its side effects or imply the use of lower doses of baclofen [183,184].…”
Section: Discussionmentioning
confidence: 99%